Is My Boss Really Listening to Me? The Impact of Perceived Supervisor Listening on Emotional Exhaustion, Turnover Intention, and Organizational Citizenship Behavior - Lloyd, Karina J. (Journal of business ethics, 2015)
Little is known empirically about the role of supervisor listening and the emotional conditions that listening facilitates. Having the opportunity to speak is only one part of the communication process between employees and supervisors. Employees also react to whether they perceive the supervisor as actively listening. In two studies, this paper examines three important outcomes of employee perceptions of supervisor listening (emotional exhaustion, turnover intentions and organizational citizenship behavior directed toward the organization). Furthermore, positive and negative affect are investigated as distinct mediating mechanisms. Results from Study 1 revealed that employee perceptions of supervisor listening reflected supervisors’ self-ratings of how they listen to their employees and these perceptions were associated with the three work outcomes. Study 2 replicated the findings in a larger sample and found evidence for two explanatory mechanisms. Positive affect mediated the effects of perceived supervisor listening on organizational citizenship behavior and turnover intention, whereas negative affect mediated listening effects on emotional exhaustion and turnover intention. Implications for organizational research and managerial practice concerning workforce sustainability are discussed.